Analysis of the Coalbed Methane Reservoir Characteristics in the Ordos Basin - Zhang, Hong (International Journal of Natural Resources and Environmental Studies, 2025)
Coalbed methane (CBM) broadly refers to all natural gas found in coal-bearing strata, while the more specific definition pertains to methane gas trapped within coal seams and the adjacent tight sandstone reservoirs. In China, there is significant potential for the "increase of reserves and production" of coalbed methane, which holds substantial strategic value for national energy security. However, the current resource discovery and utilization rates remain extremely low, revealing a significant disparity. This paper analyzes the six fundamental geological characteristics of coalbed methane, including its gas storage state, reservoir diversity with strong cyclicity, complex gas-water distribution within coal seams, variable relationships between source rocks and cap rocks, and the fragile dynamic equilibrium of overlapping gas-bearing systems. Using the northern and eastern parts of the Ordos Basin, particularly the Linxing and Ma-4 segments, as case studies, this paper examines the characteristics of coalbed methane accumulation, source rock conditions, reservoir conditions, and fracture development. The findings provide insights into the coalbed methane accumulation characteristics of the Ordos Basin and offer valuable reference for future CBM exploration and exploitation in China.